2015
DOI: 10.1063/1.4930281
|View full text |Cite
|
Sign up to set email alerts
|

Simulating plasma production from hypervelocity impacts

Abstract: Hypervelocity particles, such as meteoroids and space debris, routinely impact spacecraft and are energetic enough to vaporize and ionize themselves and as well as a portion of the target material. The resulting plasma rapidly expands into the surrounding vacuum. While plasma measurements from hypervelocity impacts have been made using ground-based technologies such as light gas guns and Van de Graaff dust accelerators, some of the basic plasma properties vary significantly between experiments. There have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 36 publications
5
31
2
Order By: Relevance
“…For ions, the bias voltage increased to −5 and −20 V reduces the fraction of escaping ions to about 55% and 25%, respectively, compared to the 0 V bias case (Figures 3g and 3h). On the other hand, the hydrodynamic simulations of dust impact events performed by Fletcher et al (2015) predicted significantly lower temperatures (about 4 eV at 20 km/s impact speed) than those reported by Collette et al (2016), or in this article. The ion energies were calculated from the widths of mass lines measured in a linear time-of-flight analyzer setup.…”
Section: Electron and Ion Temperaturescontrasting
confidence: 64%
See 1 more Smart Citation
“…For ions, the bias voltage increased to −5 and −20 V reduces the fraction of escaping ions to about 55% and 25%, respectively, compared to the 0 V bias case (Figures 3g and 3h). On the other hand, the hydrodynamic simulations of dust impact events performed by Fletcher et al (2015) predicted significantly lower temperatures (about 4 eV at 20 km/s impact speed) than those reported by Collette et al (2016), or in this article. The ion energies were calculated from the widths of mass lines measured in a linear time-of-flight analyzer setup.…”
Section: Electron and Ion Temperaturescontrasting
confidence: 64%
“…The ion energies were calculated from the widths of mass lines measured in a linear time-of-flight analyzer setup. On the other hand, the hydrodynamic simulations of dust impact events performed by Fletcher et al (2015) predicted significantly lower temperatures (about 4 eV at 20 km/s impact speed) than those reported by Collette et al (2016), or in this article. Field (B ≠ 0) Now let us investigate the variation of the signals with the magnetic field.…”
Section: Electron and Ion Temperaturescontrasting
confidence: 64%
“…a frame rate of 270 000/s and luminescence of plasma was observed at the impact point. The generation of plasma has been observed in the impact test of other materials (Song et al 2016;Fletcher et al 2015). However, to the best of the authors' knowledge, this is the first time it is observed in cementitious material.…”
Section: High-speed Impact Testmentioning
confidence: 85%
“…The amplitude strongly increases with the velocity (power ranges from 3.8 to 4.2; Collette et al, 2014) and linearly with mass (power of 3 in size). The fact that impacts of smaller dust grains are much more probable than impacts of bigger ones (Grün et al, 1985) implies that we should expect much more events with small amplitudes for events related to the dust impact. It is possible to see that the pulses with higher amplitudes are less frequent than smaller ones and it is in a good agreement with the assumption that the pulses are generated by the dust impacts.…”
Section: Amplitudes Of the Pulsementioning
confidence: 99%